2020
DOI: 10.3390/w12030765
|View full text |Cite
|
Sign up to set email alerts
|

A Definition of Aquaculture Intensity Based on Production Functions—The Aquaculture Production Intensity Scale (APIS)

Abstract: Aquaculture intensity has been used for years as a means to gauge how much production a site makes using three terms: extensive, semi-intensive and intensive aquaculture production systems. The industry has a relatively coordinated understanding of these terms, but an explicit general definition does not seem to exist. This paper aims to use three kinds of production function groups; the input, treatment and output functions to describe and define the terms extensive, semi-intensive and intensive explicitly. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 59 publications
1
14
0
1
Order By: Relevance
“…Furthermore, our study showed the average production, shrimp feed used, lime used and labour (h) per yield in the intensive farm were higher than the semi‐intensive systems (Table 3). Findings are congruent with the results of Carballo et al (2008) and Oddsson (2020), where authors differentiated characters between semi‐intensive and intensive systems. In the stochastic frontier model, the feed cost correlated positively with TE in the intensive system (Table 1).…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, our study showed the average production, shrimp feed used, lime used and labour (h) per yield in the intensive farm were higher than the semi‐intensive systems (Table 3). Findings are congruent with the results of Carballo et al (2008) and Oddsson (2020), where authors differentiated characters between semi‐intensive and intensive systems. In the stochastic frontier model, the feed cost correlated positively with TE in the intensive system (Table 1).…”
Section: Discussionsupporting
confidence: 91%
“…Mangrove forests absorb CO2 and produce O2 at a relatively high rate compared to other forest types (Hossain and Nuruddin 2016). In addition, mangroves have high adaptability when combined with an anaerobic environment and conditions (Oddsson 2020), resulting in significant long carbon storage potential (Murdiyarso et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…A traditional cultivation system is the simplest type of system and is characterized by low stocking densities, natural food feeding, relatively small business capital, and cultivation activities that are more dependent on natural conditions (Anras et al 2010). Semi-intensive and intensive methods are characterized by high stocking densities, a combination of natural and artificial feeds, the presence of periodic water quality measurements, and greater business capital (Oddsson 2020). In response to the high demand for whiteleg shrimp, many farmers have implemented intensive systems because they can significantly increase shrimp production (Nguyen et al 2020).…”
Section: Introductionmentioning
confidence: 99%